Amateur boxing coaches perceptions of the technical components of straight punches - Britton, R.; Bolger, R.; Hanlon, M.; Healy, R.; Beattie, K.; Tierney, G. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Boxing coaches` experiential knowledge from a variety of environments can be used to affirm quantitative findings and shed light on areas for future investigation. Five interviews were conducted with expert amateur boxing coaches on straight punch technique in amateur boxing. Reflexive thematic analysis derived higher order themes regarding the contributing body segments to straight punches, including the lower body, core and upper body. Coaches described punches as starting from the ground and transitioning toward the upper body ending upon impact via the fist. Coaches identified that important components of straight punches include stepping in, rotating the rear foot, rotating the hips and pronating the hand as well as bringing the shoulder up to protect the chin. They also stated that straight punch technique may change when used in combinations compared to single punches. This research highlights the important technical components of straight punches, this can help to inform boxing coaches, strength and conditioning staff and boxers of straight punching technique. Movements identified in this study can be observed in future kinetic and kinematic analysis of punching technique to better understand and interpret findings.